Hierarchically nanoporous carbons derived from empty fruit bunches for high performance supercapacitors - Choi, Min Sung; Park, Sulki; Lee, Hyunjoo; Park, Ho Seok (KOREAN CARBON SOC, 2018)
Hierarchically porous, chemically activated carbon materials are readily derived from biomass using hydrothermal carbonization (HTC) and chemical activation processes. In this study, empty fruit bunches (EFB) were chosen as the carbon source due to their sustainability, high lignin-content, abundance, and low cost. The lignin content in the EFB was condensed and carbonized into a bulk non-porous solid via the HTC process, and then transformed into a hierarchical porous structure consisting of macro- and micropores by chemical activation. As confirmed by various characterization results, the optimum activation temperature for supercapacitor applications was determined to be 700 degrees C. The enhanced capacitive performance is attributed to the textural property of the extremely high specific surface area of 2861.4 m(2) g(-1). The prepared material exhibited hierarchical porosity and surface features with oxygen functionalities, such as carboxyl and hydroxyl groups, suitable for pseudoca-pacitance. Finally, the as-optimized nanoporous carbons exhibited remarkable capacitive performance, with a specific capacitance of 402.3 F g(-1) at 0.5 A g(-1), a good rate capability of 79.8% at current densities from 0.5 A g(-1) to 10 A g(-1), and excellent life cycle behavior of 10,000 cycles with 96.5% capacitance retention at 20 A g(-1).